Late nesting of the common swift Apus apus and the pallid swift Apus pallidus in Bulgaria - Stoyanov, George (Acrocephalus, 2003)
Until recently, Swifts Apus apus had not been known to breed in Ljubljana and other larger towns in central Slovenia. This is surprising in the light of theoften cited omnipresence of breeding Swifts in human settlements in Europe.Furthermore, Swifts are common breeding birds in SW in NE Slovenia. In the years 1999-2001, three breeding sites were discovered in Ljubljana, all inactive House Martin Delichon urbica colonies. One nest was found in a House Martin's nest. The long period of non-breeding of Swifts in Ljubljana thus cannot be explained by unfavourable ecological conditions. It is more likely that the synanthropic colonization of central Slovenia is a process that has not ended as yet. This hypothesis is supported by similar patterns observed insome other synanthropic species, primarily House Martin, which colonized Ljubljana only two decades prior to the Swift.
Keywords: Birds; Gnezdenje živali; Nesting behavior; Ptice; bird; gnezdenje; hudourniki; Ljubljana